Descriptive Study of Reverse Logistics (RL) Activities and Ceramic Waste Innovation at PT. Lucky Indah Keramik - Sawitri, Yulia; Maizi, Hazful; Malahayati, Aisyah Juliawulan (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aims to analyze the implementation of reverse logistics in handling ceramic tableware products at PT. Lucky Indah Keramik, from end users back to the company. This activity provides benefits such as waste reduction, product cycle optimization, resource utilization, and improved customer satisfaction. The research method uses a descriptive approach, analyzing five dimensions: What, How, Who, Where, and Why and Why Not to evaluate the company's reverse logistics practices. The results indicate that PT. Lucky Indah Keramik has established clear return procedures, covering inspection flow, reverse logistics design, stakeholders, locations, motivations, obstacles, and corrective actions. The company also strives to optimize reverse logistics through reuse, repair, remanufacturing, and recycling to create an efficient and eco-friendly industry. Unusable ceramic waste is repurposed as aggregate material or handicrafts, minimizing environmental impact. The study concludes that PT. Lucky Indah Keramik's reverse logistics system operates systematically, supporting operational efficiency and environmental sustainability.